Long-Term Antecedents and Outcomes of Perceived Control - Frank J. Infurna; Denis Gerstorf; Nilam Ram; Jürgen Schupp; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Perceived control plays an important role in shaping development throughout adulthood and old age. Using data from the adult lifespan sample of the national German Socio-Economic Panel (SOEP; N > 10,000, covering 25 years of measurement), we explored long-term antecedents, correlates, and outcomes of perceived control and examined if associations differ with age. Targeting correlates and antecedents of control, findings indicated that higher concurrent levels of social participation, life satisfaction, and self-rated health as well as more positive changes in social participation over the preceding 11 years were each predictive of between-person differences in perceived control. Targeting health outcomes of control, survival analyses revealed that perceived control predicted 14-year hazard rates for disability (n = 996 became disabled) and mortality (n = 1,382 died). The effect for mortality, but not for disability, was independent of socio-demographic and psychosocial factors. Overall, we found very limited support for age-differential associations. Our results provide further impetus to thoroughly examine processes involved in antecedent-consequent relations among perceived control, facets of social life, well-being, and health.
Keywords: 330; Control; lifespan development; disability; mortality; psychosocial; Persönlichkeitspsychologie; Wahrnehmung; Altersgruppe